Vaccination dropout and wealth related inequality among children aged 12–35 months in remote and underserved settings of Ethiopia: a cross-sectional evaluation survey - Shiferie, Fisseha; Gebremedhin, Samson; Andargie, Gashaw; Tsegaye, Dawit A.; Alemayehu, Wondwossen A.; Mekuria, Legese Alemayehu; Wondie, Tamiru; Fenta, Teferi Gedif (Frontiers in Pediatrics, 2023)
Background: Vaccination is one of the most cost-effective public health interventions that prevents millions of deaths. Although immunization coverage is increasing globally, many children in low-and middle-income countries drop out of the vaccination continuum. This study aimed at determining vaccination dropout rates and predictors in children aged 12 to 35 months in remote and underserved areas of Ethiopia.This study was part of a cross-sectional evaluation survey that was conducted in 2022 in Ethiopia. The study settings include pastoralist, developing & newly established regions, conflict affected areas, urban slums, internally displaced populations and refugees. A sample of 3,646 children aged 12 to 35 months were selected using a cluster sampling approach. Vaccination dropout was estimated as the proportion of children who did not get the subsequent vaccine among those who received the first vaccine. A generalized estimating equation was used to assess determinants of the dropout rate and findings were presented using an adjusted odds ratio with 95% confidence interval. Concentration curve and index were used to estimate wealth related inequality of vaccination dropout.Results: A total of 3,646 caregivers of children participated in the study with a response rate of 97.7%. The BCG to Penta-3 (52.5%), BCG to MCV-2 (57.4%), and Penta-1 to Penta-3 (43.9%) dropouts were all high. The highest Penta-1 to Penta-3 dropout rate was found in developing regions (60.1%) and the lowest was in urban slums (11.2%). Caregivers who were working outside their homes [AOR (95% CI)=3.67 (1.24-10.86)], who had no postnatal care follow-up visits [AOR (95%CI)=1.66 (1.15-2.39)], who did not receive a service from a skilled birth attendant [AOR (95%CI)=1.64 (1.21-2.27)], who were older than 45 years [AOR (95% CI)=12. 49 (3.87-40.33)], and who were less gender empowered [AOR (95%CI)=1.63 (1.24-2.15)] had increased odds of Penta-1 to Penta-3 dropout. The odds of dropout for children from poor caregivers was nearly two times higher compared to their wealthy counterparts [AOR (95%CI)=1.87 (1.38-2.52)].Vaccination dropout estimates were high among children residing in remote and underserved settings. Poor wealth quintile, advanced maternal age, low women empowerment, and limited utilization of maternity care services contributed to vaccination dropout.